Calculation and Optimal Design of Rotor Shaft Torsional Vibration of a Helicopter Transmission System - De Ni; Tuanjie Zhong; Jing Wei; Miaofei Cao; Bin Peng (Jixie chuandong)
The rotor shaft vibration of the helicopter transmission system is an important factor affecting its operational reliability. In order to improve the safety margin of torsional vibration of the rotor shaft system of a coaxial counter-rotating double-rotor transmission system，under the premise of considering the lightweight design，by changing the shaft section diameter size or changing the excitation frequency makes the natural frequency of torsional vibration stagger with the excitation frequency，so as to avoid resonance and realize the optimized design of shafting torsional vibration frequency modulation. The torsional vibration safety margin of the optimized shaft system reaches more than 10%，and the torsional vibration characteristics are effectively improved. The calculation and optimization methods have certain guiding significance for the improved design of the rotor shafting of the helicopter transmission system.